Strategies for Empowering Local Communities through Sustainable Ecotourism Development in Indonesia - Awaluddin, M.; Cahaya, A.; Ashar, Ade Fariq; Abubakar, Andi; HM, Syarifuddin (Universitas Negeri Makassar, 2024)
This study explores the role of sustainable ecotourism in empowering local communities in Indonesia, focusing on the economic and environmental benefits it offers. As Indonesia is home to diverse natural resources and cultural heritage, ecotourism has emerged as a promising sector to support both environmental conservation and community development. The primary objective of this research is to identify strategies for enhancing the impact of ecotourism projects, ensuring they provide economic opportunities for local populations while promoting sustainability. The research employs a qualitative approach, utilizing case studies from various ecotourism projects across Indonesia, where in-depth interviews and focus group discussions were conducted with key stakeholders, including local residents, ecotourism operators, and government officials. The study also involves document analysis of relevant policies and reports to understand the regulatory framework surrounding ecotourism. The findings reveal that community participation in ecotourism planning and management is essential for both economic empowerment and effective conservation. However, challenges such as environmental degradation, over-tourism, and inequitable benefit distribution persist. The research highlights the need for stronger regulatory oversight, fair profit-sharing mechanisms, and policy support to address these issues. Ultimately, this study underscores the potential of sustainable ecotourism as a tool for both economic development and environmental protection, provided that collaborative efforts among local communities, government, and private stakeholders are in place.